Autodesarrollo y conservación de los recursos naturales de la Microcuenca Zamora Huayco - González Ramírez, Cecilia Anabell (2016)
The Microbasin Zamora Huayco, it is located in the National Park Podocarpus, in his average part one finds the source of water capture for the human consumption of Loja's city, there belongs to the parish San Sebastian, canton Loja, province of Loja, the same one supplies in 60 % the population with this vital liquid. The inadequate use of the natural resources in the microbasin owes to the ignorance of the importance and conservation of the nature and the limited environmental conscience; these constitute the principal problems in the area of study, which generates an environmental degradation and the decrease in the quality of life of the settlers of the sector and the citizenship lojana. On the basis of this problematics the accomplishment of the project appeared "Autodevelopment and conservation of the natural resources of the Microbasin Zamora huayco ", same that contemplates the following aims: · Diagnoses the situation of the community participation across theoretical and methodological foundations in the suitable use and conservation of the natural resources of the microbasin Zamora Huayco. · To elaborate an offer of Community Autodevelopment that propitiates the participation of the inhabitants of the microbasin Zamora Huayco in the use and conservation of the natural resources and in the diversification of the offer of goods and alternative services. 1.For the fulfillment of the objectives of the Community Self-Development methodology was used. Initial exchange with the subject applicant professional action: We contacted community leaders with whom the periodization of community history was conducted to understand changes in the ecosystem, for that secondary sources were processed (previous studies in the study area), interviews and surveys reporting on developments in the area were conducted to study. 2. Exploration stage : the different levels of organization , social practices and their influence on the functioning of the 7 environment and the conservation status were identified for this informant interviews were conducted with this base summary tables of existing organizations were developed , they identified the main problem of the study area and the interrelationships between this and the community , to do interviews was made to determine the current use of the medium and its evolution, field visits and in-depth analysis , characterization of the community ( lifestyles ) , information from secondary sources (census, thematic maps, topographic , aerial photographs, studies , etc.) are reviewed, the leaders of each community helped with the approach to each family sector , reasoned sample (representing families settled each of the studied catchments ) , interviews with producers , visits were made to families which allowed direct observation of the life of the community. 3. Diagnosis and solutions: five workshops with residents of the watershed, where the perception of the residents, their needs, priorities, expectations, problems requiring priority solution and individuals most affected scenarios, these were met were conducted developed the diagnosis of the problem, through spaces of group reflection, presentation and SWOT matrix analysis, identification and prioritization of problems and determination of actions to perform. This gave way to the construction of the proposed Community Self-development with the active participation of the inhabitants of the Microcuenca Huayco Zamora. The results of the initial exchange according to the interview, about community history and environmental changes indicate that the catchment El Carmen in the beginning involved a single hacienda later passed into the hands of the laborers working at the site, who took possession of these lands and have been populating with their families over the years, the changes experienced in the catchment are in the creek pollution, decreased water flow and quality, increasing population and disappearance of animal species and vegetables. San Simon was used as a cattle ranch, being acquired this land by its owners became Education Center and Ecological Reserve, whose aims are focused on conservation and education, as their owners took possession of the place have initiated actions to reduce environmental issues, Mendieta said in its people suffered major changes as the decline in 8 the quality and quantity of water, population growth and the reduction of green areas. The level of organization in each catchment is properly structured three have a central committee who are responsible for the management of each sector. In the exploration stage necessary data allowed to have on hand a characterization of communities in the study area as collected : social practices carried out in El Carmen are linked to agriculture and livestock and a small percentage to the construction, San Simon to become an Educational Unit is devoted entirely to education based on environmental conservation , the population of Mendieta is mostly engaged in commerce and construction, a lower percentage to agriculture, the main problem area identified study, as weak organizations and low participation of villagers in the management of the watershed , the catchments facing pollution of streams mainly by the presence of human and animal waste , soil erosion and suffer constant landslides, the air of discomfort by product odor livestock activities , flora and fauna have been highly affected by the introduction and disappearance of species, which has been generated in these areas forest degradation , loss of biodiversity , reduction in the quantity and quality of water and low agricultural production and productivity. In the diagnosis stage through participation spaces existing problems at the site was determined from the perception of the villagers, the SWOT matrix was constructed, alternative solutions were proposed, which are themselves reflected in a proposed same participatory management looking for the overall improvement of the quality of life of the inhabitants and the conditions of the natural resources of the watershed. The proposal includes six programs; each program contains its objectives, issues and activities to do.